2017
DOI: 10.3389/fimmu.2017.00433
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin Gallate Targets Notch to Attenuate the Inflammatory Response in the Immediate Early Stage in Human Macrophages

Abstract: Inflammation plays important roles at different stages of diabetes mellitus, tumorigenesis, and cardiovascular diseases. (−)-Epigallocatechin gallate (EGCG) can attenuate inflammatory responses effectively. However, the immediate early mechanism of EGCG in inflammation remains unclear. Here, we showed that EGCG attenuated the inflammatory response in the immediate early stage of EGCG treatment by shutting off Notch signaling and that the effect did not involve the 67-kDa laminin receptor, the common receptor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…To verify these results in mouse macrophages, we examined the expression of Notch-1/2 by Western blot analysis. Similar to previous results (18), EGCG attenuated the expression of Notch-1/2 (Fig. 4B, C).…”
Section: Egcg Could Target Notch To Inhibit the Inflammatory Responsesupporting
confidence: 91%
See 2 more Smart Citations
“…To verify these results in mouse macrophages, we examined the expression of Notch-1/2 by Western blot analysis. Similar to previous results (18), EGCG attenuated the expression of Notch-1/2 (Fig. 4B, C).…”
Section: Egcg Could Target Notch To Inhibit the Inflammatory Responsesupporting
confidence: 91%
“…4A), and release from mouse macrophages of the cytokines induced by LPS was inhibited by EGCG. In our previous study (18), we found that EGCG attenuated the immediate early inflammatory response through the Notch pathway in human macrophages differentiated from THP-1 cells. To verify these results in mouse macrophages, we examined the expression of Notch-1/2 by Western blot analysis.…”
Section: Egcg Could Target Notch To Inhibit the Inflammatory Responsementioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, the inhibition of NF‐κB has been suggested as a main target for the treatment of intestinal inflammatory reactions and maintenance of intestinal barrier function (Suenaert et al, ). Many researches demonstrated that EGCG significantly reduced inflammation by inhibiting NF‐κB pathways (Wang et al, ). Present study also showed that supplementation of EGCG to heat‐stressed broiler diet presented positive effect on villus height, crypt depth and the villus/crypt ration, as well as expression of Muc2 and Claudin‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds have received great attention for their purported anti‐cancer effects, frequently mediated via Notch inhibition. For instance, xanthohumol, butein, honokiol, diallyl trisulfide, quercetin, and (−)‐epigallocatechin gallate have all shown Notch inhibitory effects in vitro. Curcumin, an extensively studied component of turmeric, exerts Notch‐inhibiting effects by downregulating γ‐secretase component expression .…”
Section: Strategies For Notch Inhibitionmentioning
confidence: 99%